Visible Light Activity of Titania Photocatalyst: A Brief Review - Lee , Burtrand I. (Current Overview on Science and Technology Research Vol. 7, 2022)
Since sunlight is a fantastic source of clean energy, research is being done on effective photocatalysts that are active in visible light to capture or convert the energy. Under UV light, Titania is widely used as a photocatalyst and photosemiconductor. Growing efforts have been made to make it visible light active. Some factors affecting the photocatalytic activity of titania active under visible light, in terms of crystallography, are presented in this review article. Several recommendations for a better visible light active titania are presented in light of current advancements.